Faktor Histeria dalam Kalangan Remaja Sekolah (Sains Humanika, 2012)
Hysteria in Malaysia is a social phenomenon that has been long happening in the community. The incident gives a deep psychological impact on the students and schools. The purpose of this study is to identify factors that cause the symptoms of hysteria occurred among the teenagers in schools. One of the factors to be the cause of these symptoms are psychological and religious factors. The study is conducted in one of the secondary schools in Selangor, involving a sample of 54 students who have had hysterics. The study methodology uses a survey design with data collection techniques in a questionnaire. A pilot study had been done before the questionnaires were distributed and acquired Alpha Cronbach value of 0.91, exceeds > 0.9. The results show, psychological and religious factors exist as a causing factor in the symptoms of hysteria among the school teenagers. Among the psychological factors that have the highest percentage is to be under pressure (75.9%) and anxiety in making decision (79.6%). In terms of religious factors, the student is lazy to perform Ibadah (66.7%) and performing prayers inadequately which is less then five times a day whereby only 20.4% of respondents who admitted that they perform prayers five times a day. As a whole, the study has discovered that hysteria can occur when the teenager’s psychology is disturbed and the lack of religious practice.
Keywords: Hysteria; psychology; emotional disturbance